The great reversal : how we let technology take control of the planet - Tabachnick, David (University of Toronto Press, 2012)
As the rise of technology threatens our very humanity, Tabachnick emphasizes that we still may have time to recover and develop these capacities -- but we must first decide how far we want to allow technology to determine our existence and our future.